(3GdGSJbQGQ GdGbJUGOi hGdeSJhi GdeSJgOa dGfJGL hJUOjQ GdHQJbGd ai eUQs - (3GdHhdhfi, hMjO eMeO(B.s (2004)
(3GSJgOa GdHMK OQGSI GdJYQa Ydi GdGSJbQGQ GdGbJUGOi hGdeSJhi GdeQZhH dGfJGL GdHQJbGd NdGd GdaJQI ef (B1982-2000 (3, hJe ai gPG GdHMK GSJNOGe HYV WQb GdJMdjd GdGbJUGOi hGdGMUGFj(B.s
(3jMJhj Ydj eQGLY(B.s
(3edNU HGddZI GdGfLdjRjI(B.s
1
Keywords: (3GdHQJbGds -- (3EfJGLs -- (3eUQs; (3GdHQJbGds -- (3JLGQIs -- (3eUQs